The Effect of Transformational and Transactional Leadership on Employee Performance Mediated by Innovative Work Behavior - Sakti, Oktaviana Puteri; Kurniawati, Desi Tri; Rahayu, Mintarti (Green Publisher Indonesia, 2023)
The purpose of this research is to examine the effect of transformational and transactional leadership on the employee performance of chicken slaughterhouse with the mediation of innovative work behaviour. This study was conducted on Chicken Slaughterhouse PT. XYZ, from which 120 employees were selected as the respondents using purposive sampling. The data was harvested from questionnaires and was analyzed using Partial Least Squares in SmartPLS 3.2.9. The results of the study show that transformational leadership has no direct significant effect on employee performance, whereas transactional leadership has a direct positive and significant effect on employee performance. Furthermore, the research results also show a positive and significant effect of transformational and transactional leadership on innovative work behavior and innovative work behavior has a positive and significant effect on employee performance. Interestingly, innovative work behavior is able to mediate the influence of transformational and transactional leadership on employee performance.